Estudo taxonômico de Lamiaceae Martinov no Estado da Paraíba – Brasil - Monteiro, Fernanda Kalina da Silva (2018)
Lamiaceae has cosmopolitan distribution and is predominantly associated with Mediterranean region and Southwestern Asia. It comprises 7,500 species in 300 genera, of which 46 genera and 525 species are registered in Brazil, commonly associated with open environments. In Paraíba, until the moment were recorded 24 native species in 12 genera. Due to the representativeness of this family associated to its economic and medicinal importance, besides the lack of taxonomic studies, the present work includes the taxonomic survey of Lamiaceae native to Paraíba, Brazilian northeast. For this purpose, field visits were carried out and, mainly, exsiccatae deposited at the herbaria of Paraíba (ACAM, CSTR, EAN and JPB) and Pernambuco states (IPA and PEUFR) as well as comparisons with virtual herbaria images (B, G, HUEFS, K, MAC, NY, RB, SP and UFP) available in the Specieslink and Virtual Herbarium of Plants and Fungi (Reflora) databases. During the field works, in several municipalities of Paraíba, samples were obtained with flowers and or fruits and observations were made 'in loco' of the individuals. The samples were conditioned and dried according to the usual techniques in taxonomic studies and later incorporated into the ACAM Herbarium collection, Campus I, State University of Paraíba (UEPB). In total, 26 species distributed in 12 genera were recorded (Aegiphila Jacq., Amasonia L.f., Eplingiella Harley & J.F.B. Pastore, Hypenia (Mart. Ex Benth.) Harley, Hyptis Jacq., Leptohyptis Harley & J.F.B. Pastore, Marsypianthes Mart. Ex Benth, Medusantha Harley & J.F.B. Pastore ex Benth., Mesosphaerum P. Browne, Ocimum L., Rhaphiodon Schauer e Vitex L.) and three subfamilies: Ajugoideae (five spp.), Nepetoideae (16 spp.) and Viticoideae (five spp.). Morphological descriptions, identification keys and illustrations of the diagnostic characters of the species are provided. Geographic distribution, environment, flowering and fruiting of these species are also presented.